Maritime Insecurities in the Sulu and Sulawesi Seas - Rahmadanu Pradityo (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
The increase in the threat of crime in the Sulu and Sulawesi Seas in recent yearshas caused the countries bordering the two seas, namely Indonesia, Malaysia, andthe Philippines, to agree to form a trilateral cooperation called INDOMALPHIin 2016. The 2017 attack on Marawi City, Philippines, by a group affiliated withan international terrorist network has added to the security vulnerabilities in theSulawesi and Sulu Seas. Despite being constrained by the COVID-19 pandemic,trilateral cooperation continues with all its limitations, namely through onlinemeetings. Until 2022, through the Ministry of Defense, the three countries willstrengthen the trilateral cooperation agreed in Malaysia again. This study uses amaritime insecurity concept framework with a qualitative approach that uses aliterature study data collection method consisting of books, journal articles,official ASEAN websites, and online news sites. The results of the study showthat there are still threats that cause maritime insecurity, which encourages thestrengthening of trilateral cooperation by Indonesia, Malaysia, and thePhilippines in 2022 in order to realize maritime security in the Sulu and SulawesiSea regions.